Das Ländliche als kulturelle Kategorie: Aktuelle kulturwissenschaftliche Perspektiven auf Stadt-Land-Beziehungen - Trummer, Manuel; Decker, Anja (transcript, 2020)
Living in the countryside: joy or frustration? Ethnological perspectives on the boom of the rural as a life-world experience and interpretation category as well as its cultural-analytical framing.